English Department Students' Most frequent Errors at Swadaya Gunung Jati University, Cirebon - Rozak, Diana Rahmawati (Universitas Swadaya Gunung Jati, 2013)
This study focuses on error analysis of second year students from four classes of English department at Universitas Swadaya Gunung Jati Cirebon. A total of one hundred and four of enrolled students participated. They were asked to interview someone about his or her profession and personal life and write the report in three paragraphs. Both interview and report writing conducted in group of three or four. Data collected from interlingua and intralingua categories and were analyzed to find the most frequent error of these students. The frequent error is obtained by calculating the number of error from each category and presented in form of percentage. The findings show that the most frequent error is from the interlingua aspect which is the selection of wrong word in the case of divergence between L1 and L2 (50%). The result will be beneficial for selecting treatment so that the students can improve their mastery of English.